Irrigation depth and silicate fertilisation in green maize - Nojosa Dias Fernandes, Chrislene (Revista Ciência Agronômica, 2021)
The successful use of irrigation depends on the adoption of efficient management, which in turn depends on determining the correct amount of irrigation water. Due to the water scarcity seen in recent years, there is an obvious need for strategies that would make it possible to reduce the amount of water applied to crops with no reduction in productivity. Among such strategies, the application of silicon, which is associated with several beneficial effects for the plant, can increase water use efficiency. The aim of the present work was to study irrigation-depth management versus silicon doses via foliar application in green maize under a semi-arid climate. The experiment was conducted from August to November 2017 in an area of the Federal Institute of Ceará, Iguatu Campus, Ceará, using the AG1051 hybrid. The experimental design was of randomised blocks, comprising split plots and four blocks. Five irrigation depths (50, 75, 100, 125 and 150% of the ETc) were evaluated in the plots and four doses of silicon (50, 100, 150 and 200% of the recommended dose) were evaluated in the subplots. The following growth variables were analysed 15, 30, 45, 60 and 75 days after sowing (DAS): leaf dry weight, stem dry weight, and total dry weight; the production variables, evaluated at 81 DAS, were ear diameter and ear length with no husks, ear weight with and with no husks, and productivity. The application of silicon had no significant effect on the variables, while the irrigation depths afforded linear growth for each variable, with the highest productivity (10,459.3 kg ha-1) obtained for the greatest irrigation depth of 600 mm (150% of the ETc).